Medial Condyle Fracture (Kilfoyle Type III) of the Distal Humerus with Transient Fishtail Deformity after Surgery - Motoki Sonohata; Takema Nakashima; Hiroaki Suetsugi; Masaru Kitajima; Masaya Ueno; Masaaki Mawatari (Case Reports in Orthopedics)
A “Fishtail deformity” is one of the well-known complications following pediatric lateral condyle or supracondylar fractures of the humerus. We herein report a case of medial condyle fracture (Kilfoyle type III) in an 11-year-old boy. He had a transient “fishtail deformity” of the trochlear groove after open reduction and internal fixation. As occurred in the current case, the bone remodeling and the improvement of ischemia of the trochlea after medial condyle fracture may be associated with the likelihood of recovery from transient “fishtail deformity.”